Bacterial flavoprotein monooxygenase YxeK salvages toxic S‐(2‐succino)‐adducts via oxygenolytic C–S bond cleavage. (4th October 2021) - Matthews, Arne; Schönfelder, Julia; Lagies, Simon; Schleicher, Erik; Kammerer, Bernd; Ellis, Holly R.; Stull, Frederick; Teufel, Robin
Abstract : Thiol‐containing nucleophiles such as cysteine react spontaneously with the citric acid cycle intermediate fumarate to form S ‐(2‐succino)‐adducts. In Bacillus subtilis, a salvaging pathway encoded by the yxe operon has recently been identified for the detoxification and exploitation of these compounds as sulfur sources. This route involves acetylation of S ‐(2‐succino)cysteine to N‐acetyl‐2‐succinocysteine, which is presumably converted to oxaloacetate and N‐acetylcysteine, before a final deacetylation step affords cysteine. The critical oxidative cleavage of the C–S bond of N‐acetyl‐ S ‐(2‐succino)cysteine was proposed to depend on the predicted flavoprotein monooxygenase YxeK. Here, we characterize YxeK and verify its role in S ‐(2‐succino)‐adduct detoxification and sulfur metabolism. Detailed biochemical and mechanistic investigation of YxeK including 18 O‐isotope‐labeling experiments, homology modeling, substrate specificity tests, site‐directed mutagenesis, and (pre‐)steady‐state kinetics provides insight into the enzyme's mechanism of action, which may involve a noncanonical flavin‐N5‐peroxide species for C–S bond oxygenolysis. Abstract : S ‐(2‐succino)‐adducts arise for instance from the spontaneous addition of cysteine to fumarate, which affords S ‐(2‐succino)cysteine. Recently, a disposal route for this toxic metabolite was discovered in Bacillus subtilis, in which N ‐acetyl‐ S ‐(2‐succino)cysteine is formed and presumably converted by the predicted two‐component flavoprotein monooxygenase YxeK. Here, we demonstrate that FMN‐dependent YxeK oxygenolytically cleaves the C–S bond of N ‐acetyl‐ S ‐(2‐succino)cysteine to produce oxaloacetate and N ‐acetylcysteine, possibly via a noncanonical flavin‐N5‐peroxide species.